Somatic and germline mutagenesis assayed by the unstable zeste-white test in Drosophila melanogaster. - Rasmuson, A.; Larsson, J. (Mutagenesis, 1992)
This investigation is an attempt to compare mutation rates in germinal and somatic cells by the use of the unstable zeste-white assay in Drosophila melanogaster. In this system it is possible to use the same genetic end point to measure both somatic mutations (aberrantly pigmented spots in the eyes of adult flies) and germinal mutations (males with aberrantly pigmented eyes). We used two mutagens, formaldehyde and methylmethane sulphonate (MMS), to induce mutations and two different routes of mutagen administration, larval feeding and adult feeding, and scored mutations in somatic as well as germinal cells. Both types of tissues were susceptible to MMS mutagenesis, showing elevated frequencies of both germline mutations and eye spots. Formaldehyde, however, gave no increase in the germinal mutation rate but caused somatic mutations. These were found after larval exposure, but also among the offspring of exposed males, as formation of delayed somatic mutations. The results show that somatic cells are much more sensitive in monitoring induced mutations than germinal cells in this system. We also found that spontaneous mutation rate among germinal cells is 200 times higher than that in somatic cells, which presumably is due to the involvement of a mobile element.